2003
DOI: 10.1007/s00122-003-1229-9
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar-specific seedling vigor and expression of a putative oxalate oxidase germin-like protein in sugar beet (Beta vulgaris L.)

Abstract: For genetic screening and breeding purposes, an in vitro germination system that reflects relative field emergence potential was used to screen for germination-enhancing and stress-induced genes from germinating seedlings from two varieties of sugar beet. Three full-length germin-like protein (GLP) gene classes were recovered from stress-germinated seedlings of a superior emerging variety. GLP gene expression, oxalate oxidase protein activity, the H(2)O(2) content of stressed seedlings, but not catalase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…It appears that bicarbonate is produced by carbonic anhydrase in the perisperm and distrib-uted to the embryo. Oxalate oxidase behaves as a marker of germination vigor in sugarbeet (54). Note also that formate dehydrogenase (arrow 86 in Fig.…”
Section: Sugarbeet Seed Proteome Exhibits Tissue-specific Featuresmentioning
confidence: 92%
“…It appears that bicarbonate is produced by carbonic anhydrase in the perisperm and distrib-uted to the embryo. Oxalate oxidase behaves as a marker of germination vigor in sugarbeet (54). Note also that formate dehydrogenase (arrow 86 in Fig.…”
Section: Sugarbeet Seed Proteome Exhibits Tissue-specific Featuresmentioning
confidence: 92%
“…It is important to note that both ACH185 and USH20 were once dominant commercial hybrids grown in Michigan, and that emergence and stand establishment were not the primary reasons for their being supplanted by newer hybrids (the reasons were substantially related to disease pressure). These two hybrids were chosen because they differ markedly in their germination characteristics under stress, both in the field and in solution (McGrath et al 2000;de los Reyes and McGrath 2003). Control (unstressed) germination tests were performed by allowing 25 seeds (four replications per seedlot) to germinate on moistened pleated filter paper (TeKrony and Hardin 1966).…”
Section: Seed Germinationmentioning
confidence: 99%
“…2). Five gene products were monitored: aamylase (as a marker for carbohydrate catabolism in germinating seeds); acetyl-CoA acyltransferase (a b-oxidation enzyme that links lipid metabolism with the glyoxylate cycle); ICL and MS as markers for the glyoxylate pathway; and a germin-like protein as a sugar beet cultivar-specific marker for stress response and seedling vigor (de los Reyes and McGrath 2003). Additional transcripts coding for key enzymes of glycolysis (fructose bisphosphate aldolase, phosphoglucomutase, triose phosphate isomerase, and glyceraldehyde 3-phosphate dehydrogenase) were also monitored, but RNA gel blots showed that transcripts coding for these enzymes were highly abundant in both hybrids, with a slight induction in solution, and thus did not exhibit clear cultivar specificity at this level of analysis (data not shown).…”
Section: Gene Expression Profiles During Seedling Germinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of a native herbivore of Nicotiana attenuata was found to be enhanced by silencing the germin-like gene (Lou and Baldwin, 2006). The recovery of GLPs from Beta vulgaris seedlings germinated under stress support their probable role during stress (De Los Reyes and McGrath, 2003).…”
Section: Introductionmentioning
confidence: 61%